2009
DOI: 10.1002/jsfa.3821
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous extract of Hibiscus sabdariffa L. decelerates acetaminophen‐induced acute liver damage by reducing cell death and oxidative stress in mouse experimental models

Abstract: It has been demonstrated that HSE can protect the mouse liver from AAP-induced injury and that the protective mechanism might involve decreasing oxidative stress and reducing cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 102 publications
1
20
0
Order By: Relevance
“…These ameliorative effects of H. sabdariffa extract may be mediated by inhibition of hepatic stellate cell activation. In accord with the preventive effects of H. sabdariffa extract’s components during the development of chemically induced hepatic damage [20, 21, 43, 49] the present study shows that H. sabdariffa extract is effective in the amelioration of STZ-induced liver fibrosis, which would confer a highly significant therapeutic advantage. Hibiscus sabdariffa extract is a composite of several antioxidants, such as protocatechuic acid [20, 50] and anthocyanins [21, 22] which prevents peroxidative liver damage.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These ameliorative effects of H. sabdariffa extract may be mediated by inhibition of hepatic stellate cell activation. In accord with the preventive effects of H. sabdariffa extract’s components during the development of chemically induced hepatic damage [20, 21, 43, 49] the present study shows that H. sabdariffa extract is effective in the amelioration of STZ-induced liver fibrosis, which would confer a highly significant therapeutic advantage. Hibiscus sabdariffa extract is a composite of several antioxidants, such as protocatechuic acid [20, 50] and anthocyanins [21, 22] which prevents peroxidative liver damage.…”
Section: Discussionsupporting
confidence: 79%
“…This potent antioxidation is thought to form the basis of many of the other healing activities of HSCE including its hepatoprotective activities. Compounds proven to have this antioxidant activity include anthocyanins and protocatechuic acid [43]. …”
Section: Discussionmentioning
confidence: 99%
“…17) Our previous investigation has also indicated that a water extract of Hibiscus sabdariffa L. could protect individuals from acetaminophen-induced liver injury by reducing oxidative stress. 18) We have shown in this study the functional components in Hibiscus sabdariffa L., and propose that HPE might be the major contributor to improving the oxidative status in AAP-induced liver damage. We have also previously demonstrated that HPE could inhibit lipopolysaccharide-induced inflammation by improving the antioxidative conditions and decelerating the inflammatory responses.…”
Section: Discussionmentioning
confidence: 57%
“…Total phenolic compounds were determined with the Folin-Ciocalteu reagent and expressed as mg gallic acid equivalent per 100 g fresh BB. 24 The total flavonoid levels were measured with aluminum chloride colorimetric method. The results are presented as mg quercetin equivalents per 100 g fresh BB.…”
Section: Total Phenolic and Total Flavonoid Assay In Fresh Bbmentioning
confidence: 99%